1983
DOI: 10.1111/j.1748-5827.1983.tb00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Condylar fractures of the humerus in the dog; a review of 133 cases

Abstract: Case histories have been reviewed of 133 dogs with condylar fractures of the humerus. The fractures were divided into three types: lateral condylar, medial condylar and intercondylar. For each type the breed and age prevalence, the cause of fracture, the method of fixation and the results of treatment have been recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
161
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(174 citation statements)
references
References 2 publications
9
161
4
Order By: Relevance
“…Non-fused and fused humeral condyles were compared in flexion and extension (Simulation 2). Overall, the finite element simulation study performed showed that the pathogenesis of condylar fractures is likely to be more complex than what has been described in the literature to date (Bardet et al, 1983;Cockett et al, 1985;Denny 1983;Rorvik 1993;Vannini et al, 1988aVannini et al, , b, 2007. As seen in clinical observations, the highest likelihood was the lateral condylar fracture (clinics 56-67%, finite element analysis 66%-70% of the time).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Non-fused and fused humeral condyles were compared in flexion and extension (Simulation 2). Overall, the finite element simulation study performed showed that the pathogenesis of condylar fractures is likely to be more complex than what has been described in the literature to date (Bardet et al, 1983;Cockett et al, 1985;Denny 1983;Rorvik 1993;Vannini et al, 1988aVannini et al, , b, 2007. As seen in clinical observations, the highest likelihood was the lateral condylar fracture (clinics 56-67%, finite element analysis 66%-70% of the time).…”
Section: Discussionmentioning
confidence: 89%
“…As seen in clinical observations, the highest likelihood was the lateral condylar fracture (clinics 56-67%, finite element analysis 66%-70% of the time). Bilateral fractures were expected in 7-18% and medial condylar fractures in 18.5-26% of all scenarios tested (clinical frequency 33-35% and 4-16% respectively) (Bardet et al, 1983;Cockett et al, 1985;Denny 1983;Rorvik 1993;Vannini et al, 1988aVannini et al, , b, 2007.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Open reduction is advocated to ensure anatomic alignment of the articular surface, allow removal of soft tissue and hematoma interposed at the fracture site, and avoid clamp interference with implant placement (ie, placing the drill bit, depth gauge, tap, and screw in the appropriate location when a condylar clamp or reduction forceps is present). Denny, et al 2 reported that 9 of 16 dogs with FLHC treated with an open technique regained full limb function. Shebitz et al 3 reviewed 125 fractures of the condyles including 61 lateral, 5 medial, and 35 T‐Y fractures.…”
mentioning
confidence: 99%